Slovak Republic : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper evaluates competitiveness in Slovakia and estimates the equilibrium real exchange rate path for the koruna. It takes stock of Slovakia's growth performance over the past decade and assesses its growth potential over the medium term. It estimates the equilibrium real exchange rate appreciation in Slovakia using cross-section and time-series methods. The paper also presents production function estimates of potential output for Slovakia that imply sustainable rates of growth of 4.5-5.0 percent over the next five years.